Impact of clinical trial participation on the survival of patients with newly diagnosed advanced ovarian cancer - Lee, Yong Jae; Lee, Jung-Yun; Nam, Eun Ji; Kim, Sang Wun; Kim, Sunghoon; Kim, Young Tae (Frontiers in Oncology, 2025)
BackgroundClinical trials provide access to novel treatments that may offer survival benefits to ovarian cancer patients. This study investigates whether clinical trial participation is associated with improved survival in newly diagnosed advanced ovarian cancer.MethodsWe retrospectively investigated patients treated for advanced ovarian cancer at Yonsei Cancer Hospital between 2019 and 2021. During this period, the standard of care included cytoreductive surgery with platinum-based chemotherapy, with or without bevacizumab, followed by maintenance therapy with PARP inhibitors or bevacizumab. This study included 202 patients with stage III-IV, 82 participated in clinical trials [DUO-O (Bevacizumab+immunotherapy (IO)+/- PARP inhibitors), KEYLYNK-001 (PARP inhibitors +IO), ATHENA (PARP inhibitors), TRU-D (IO+IO)] and 120 received standard-of-care.ResultThe median follow-up duration was 39.8 months. Disease recurrence occurred in 123 (60.9%) patients and 45 (22.3%) patients died. Among the patients in both groups, there were no significant differences in age, histologic type, stage, median CA-125 level, comorbidities, and BRCA1/2 status. There were also no differences in the incorporation of hyperthermic intraperitoneal chemotherapy, neoadjuvant chemotherapy, or residual disease after cytoreductive surgery. Clinical trial participation was associated with significantly improved progression-free survival (31.4 vs. 19.1 months; HR, 0.67; 95% CI, 0.46 to 0.97; p = 0.035) and overall survival (both not reached; HR, 0.54; 95% CI, 0.31 to 0.93; p = 0.024) compared to standard of care.ConclusionClinical trial participation was associated with improved survival compared with standard of care in patients with newly diagnosed advanced ovarian cancer.